Tumefactive Fibroinflammatory Lesion of the Neck with Progressive Invasion of the Meninges, Skull Base, Orbit, and Brain - Holodny, Andrei I.; Kirsch, Claudia F.; Hameed, Meera; Sclar, Gary (American Journal of Neuroradiology, 2001)
Summary: Tumefactive fibroinflammatory lesions of the head and neck are rare. CNS involvement has not been reported. We present a histologically proven case of a tumefactive fibroinflammatory lesion that originated in the left side of the neck and progressed over 2 years to involve the meninges, the cavernous sinuses, the right temporal lobe, and the right orbit. The lesion caused destruction of the skull base and a subdural hematoma. The relationship of the present lesion to idiopathic hypertrophic pachymeningitis and Tolosa-Hunt syndrome is discussed.